Why is there Cross-Country Variation in Female Labor Force Participation Rates? The Role of Male Attitudes Toward Family and Sex Roles - Heather Antecol (Claremont McKenna College, Department of Economics, 2003)
Antecol (2000) finds that culture plays a role in explaining inter-ethnic variation in the gender gap in labor force participation rates (LFPR). However, Antecol (2000) was unable to determine what the components of culture, such as differences in preferences regarding family structure and women's role in market versus home work, actually are and how to quantify these components in an empirically meaningful manner. Using data from the 1994 International Social Survey Programme (ISSP), this paper proxies culture using a set of questions on male attitudes toward family and sex roles. I find that women are more likely to work if men in their country view female LFP in a favorable light.
Keywords: Z1; J2; 330; Female Labor Force Participation; Social Norms and Culture; Frauenerwerbstätigkeit; Vergleich; Vergleich; Industriestaaten